Efficay of probiotic and Ascorbic acid in alleviating summer stress in growing broiler rabbits - Smitha S (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 2010)
The research work was conducted to study the efficacy of probiotic (Lactobacillus casei) and ascorbic acid in alleviating summer stress in growing broiler rabbits. The study was done in the summer season from March to May. The growth performance of rabbits in summer, their physiological response to stress and the cost effectiveness of supplementing probiotic, Lactobacillus casei and ascorbic acid were studied. Twenty four weaned New Zealand White rabbits were randomly selected from Rabbit unit at Krishi Vigyan Kendra, Kerala Agricultural University, Vellanikkara were utilized for the study. They were divided into four groups of six animals each. The treatments were as follows: Treatment I (T1) - Ascorbic acid (Merck) at the rate of 200 mg per kg feed was given along with the basal diet, Treatment - 2 (T2) - Probiotic, Lactobacillus casei (Unique Biotech) containing 106 colony forming units per gram of feed was given along with the basal diet, Treatment - 3(T3) - Probiotic and Ascorbic acid at the same rate as in T2 and T3 were given along with the basal diet and Treatment - 4 (T4) - Rabbits fed with basal diet alone. The various climatic parameters studied were maximum and minimum temperature and relative humidity (morning and afternoon) in macro climate and maximum and minimum temperature, relative humidity (morning and afternoon), dry bulb temperature (morning and afternoon) and relative humidity (morning and afternoon) in micro climate. The production parameters recorded were weekly body weight, daily feed intake, average daily weight gain and feed efficiency. The physiological parameters studied were weekly respiration rate, weekly rectal temperature and monthly cortisol (faecal and serum) values (twice a month for three months). Disease incidence and mortality during the period was recorded. Cost effectiveness of supplementing probiotic and ascorbic acid was determined. The mean monthly temperature humidity index values suggested that animals were under moderate heat stress in the first (28.45±0.16) and the second month (28.50±0.22), while no stress prevailed in the third month (26.83±0.21). By one way Analysis of variance it was found that supplementation of probiotic, Lactobacillus casei and ascorbic acid had a significant effect in alleviating summer stress in rabbits. The animals in the T1 group showed significantly (P<0.05) higher overall mean daily body weight gain, overall mean feed efficiency and significantly (P<0.05) lower overall mean respiration rate and faecal cortisol level compared to T4 animals. The rabbits in T2 treatment showed significantly higher (P<0.05) final body weight, overall mean daily body weight gain, overall mean feed efficiency and significantly (P<0.05) lower overall mean respiration rate compared to T4. The rabbits in the T3 group showed significantly higher (P<0.05) final body weight, overall mean daily body weight gain, overall mean feed efficiency and significantly (P<0.05) lower overall mean faecal cortisol level compared to T4. There was no significant difference (P>0.05) between the treatments in mean feed intake, rectal temperature and serum cortisol. No disease incidence or mortality was observed during the experimental period. Supplementation of probiotic and ascorbic acid was found to be efficient in reducing the production economics. Hence it was concluded that supplementation of probiotic, Lactobacillus casei at the rate of 106 cfu per g of feed and ascorbic acid at the rate of 200 mg per kg feed in combination was found to be most effective and economic in alleviating summer stress in growing broiler rabbits.